Mouse Norovirus Infection Reduces the Surface Expression of Major Histocompatibility Complex Class I Proteins and Inhibits CD8(+) T Cell Recognition and Activation - Fritzlar, Svenja (J Virol, 2018)
Human noroviruses are highly infectious single-stranded RNA (ssRNA) viruses and the major cause of nonbacterial gastroenteritis worldwide. With the discovery of murine norovirus (MNV) and the introduction of an effective model for norovirus infection and replication, knowledge about infection mechanisms and their impact on the host immune response has progressed. A major player in the immune response against viral infections is the group of major histocompatibility complex (MHC) class I proteins, which present viral antigen to immune cells. We have observed that MNV interferes with the antigen presentation pathway in infected cells by reducing the surface expression of MHC class I proteins. We have shown that MNV-infected dendritic cells or macrophages have lower levels of surface expression of MHC class I proteins than uninfected and bystander cells. Transcriptional analysis revealed that this defect is not due to a decreased amount of mRNA but is reflected at the protein level. We have determined that this defect is mediated via the MNV NS3 protein. Significantly, treatment of MNV-infected cells with the endocytic recycling inhibitor dynasore completely restored the surface expression of MHC class I proteins, whereas treatment with the proteasome inhibitor MG132 partly restored such expression. These observations indicate a role for endocytic recycling and proteasome-mediated degradation of these proteins. Importantly, we show that due to the reduced surface expression of MHC class I proteins, antigen presentation is inhibited, resulting in the inability of CD8(+) T cells to become activated in the presence of MNV-infected cells. IMPORTANCE Human noroviruses (HuNoVs) are the major cause of nonbacterial gastroenteritis worldwide and impose a great burden on patients and health systems every year. So far, no antiviral treatment or vaccine is available. We show that MNV evades the host immune response by reducing the amount of MHC class I proteins displayed on the cell surface. This reduction leads to a decrease in viral antigen presentation and interferes with the CD8(+) T cell response. CD8(+) T cells respond to foreign antigen by activating cytotoxic pathways and inducing immune memory to the infection. By evading this immune response, MNV is able to replicate efficiently in the host, and the ability of cells to respond to consecutive infections is impaired. These findings have a major impact on our understanding of the ways in which noroviruses interact with the host immune response and manipulate immune memory.